Community Paralegals and the Pursuit of Justice - Maru, Vivek; Gauri, Varun (Social Sciences, 2018)
The United Nations estimates that four billion people worldwide lack access to justice. This book is essential for anyone who wants to change that: lawyers, researchers, policy-makers, and activists. Community paralegals demystify law and empower people to advocate for themselves. In the fight to bring justice everywhere, they are the frontline. This title is also available as Open Access.